KEHARMONISAN KELUARGA SEBAGAI PREDIKTOR SELF-ESTEEM REMAJA AKHIR DI INDONESIA: STUDI KORELASIONAL PADA MAHASISWA PESERTA PERTUKARAN MAHASISWA (PMM) TAHUN 2024 - Zulian Fikry; Adinda Fajarwati; Nurul Alya Syah Putri; Gumi Langerya Rizal (Departemen Psikologi, Universitas Negeri Padang, 2025)
Late adolescence, especially for students participating in mobility programs such as the Merdeka Student Exchange (PMM), is a critical phase in the formation of self-identity and self-esteem. Adaptation to new environments, and separation from the main support system-family-are complex psychosocial challenges. An important factor influencing self-esteem is family harmony, which includes emotional support, open communication, and a sense of security in relationships between family members. This study aims to examine the relationship between family harmony and self-esteem in students participating in PMM 2024. A quantitative approach with a correlational design was used in this study. The research subjects consisted of 100 late adolescents aged 18-21 years old who were selected using purposive sampling technique. The instruments used include a family harmony scale based on Hawari's (2006) theory and Rosenberg's (1965) self-esteem scale. Data analysis was conducted using the Spearman correlation test. The results of the analysis showed a significant positive relationship between family harmony and self-esteem (ρ = 0.400; p = 0.000). This finding indicates that the higher the level of harmony in the family, the higher the self-esteem of adolescents. This study underscores the important role of family in shaping the self-esteem of late adolescents, as well as providing practical implications for the development of self-esteem.